Heterogeneity in macroeconomics: The compositional inequality perspective - Marco Ranaldi; Elisa Palagi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This work presents a framework to jointly study individuals' heterogeneity in terms of their capital and labor endowments (endowment heterogeneity) and of their saving and consumption behaviors (behavioral heterogeneity), from an empirical perspective. By adopting a newly developed synthetic measure of compositional inequality, this work classifies more than 20 economies across over two decades on the basis of their heterogeneity characteristics. Modern economies are far from being characterized by agents with same propensities to save and con- sume and same endowments (Representative Agent systems), or by the existence of rich capital-abundant savers and poor hand-to-mouth consumers (Kaldorian systems). Our framework and results are discussed in light of the heterogeneity assumptions underlying several types of macroeconomic models with heterogeneous agents (Kaldorian, TANK & HANK, OLG, and ABM models). A negative relationship between behavioral heterogeneity and the economy's saving rate is also documented.
Keywords: D31; P10; O43; 330; Heterogeneity in Macroeconomics; Compositional Inequality